Relations between the State Civil Apparatus and Regional Heads in the Indonesian State Civil Service System - Bagus Sarnawa (Fakultas Hukum Universitas Muhammadiyah Magelang, 2022)
The purpose of this study is to ascertain the civil servant' general election neutrality model. This study used secondary data or library resources that included primary, secondary, and tertiary legal materials to accomplish its goals. This study interviewed practitioners such the National Civil Service Agency, the State Civil Apparatus Commission, and the Election Supervisory Board of the Republic of Indonesia in order to gather secondary data on personnel legislation and general elections. In this study, a statutory method was paired with a conceptual, historical, and comparative perspective. The outcomes demonstrated that civil servants' impartiality in general elections has never occurred from the start of independence till the present. This is a result of the system of subordination (unequal relations) between civil servant and political official. To balance positions between the two, it is therefore vital to separate civil servants from political officials. As a result, it is required to amend Law Number 5 of 2014 Concerning State Civil Apparatuses in order to control the separation of positions of Civil Servants and political authorities.